Micro-leakage of a Fissure Sealant Cured Using Quartz-tungsten-halogen and Plasma Arc Light Curing Units - Zahra Bahrololoomi; Ali Asghar Soleimani; Najmeh Jafari; Bentolhoda Varkesh (Tabriz University of Medical Sciences, 2014)
Background and aims. Newer curing units such as plasma arc can polymerize the sealants in much shorter curing times. The aim of this study was to compare the effect of two different curing units on the micro-leakage of a fissure sealant material. Materials and methods. Sixty two extracted premolars without caries were randomly divided into two groups of 31 samples. Occlusal surfaces of all teeth were cleansed. Then, teeth surfaces were etched by 37% phosphoric acid. After rinsing and drying, occlusal surfaces of teeth were sealed by a fissure sealant. The sealant was then cured using either a halogen light curing unit or a plasma arc curing light. After sealing, the teeth were thermocycled for 500 cycles. The teeth were then sectioned and examined for micro-leakage. Statistical analyses were performed with Mann-Whitney test. Results. There was no significant difference between two groups regarding micro-leakage (P = 0.42). Conclusion. Results showed that there was no significant difference between two different curing units. Therefore, plasma arc unit might be a useful alternative for sealant polymerization.